2018
DOI: 10.1111/1471-0528.15107
|View full text |Cite
|
Sign up to set email alerts
|

The impact of isolated maternal hypothyroxinaemia on the incidence of large‐for‐gestational‐age infants: the Ma'anshan Birth Cohort study

Abstract: Isolated maternal hypothyroxinaemia may increase the risk of large-for-gestational-age infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…Similarly, Casey et al in the USA and Breathnach et al in Ireland reported that maternal hypothyroxinemia is not associated with LBW and intrauterine growth restriction [34,39]. In addition, we showed that higher FT4 levels (>95 th percentile) decrease the risk of LGA, which is in agreement with the recent study by Zhu et al, who reported that higher FT4 levels reduce the birthweight and are inversely related to LGA risk [40]. Furthermore, we showed no significant association of FT4 levels with pregnancy complications (GDM/ICP/ PIH) and adverse birth outcomes (PTB/SGA/LGA) after adjusting for maternal age and BMI, excluding PE (adjusted OR: 0.93, 95% CI: 0.88-0.99, p < 0.05).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Casey et al in the USA and Breathnach et al in Ireland reported that maternal hypothyroxinemia is not associated with LBW and intrauterine growth restriction [34,39]. In addition, we showed that higher FT4 levels (>95 th percentile) decrease the risk of LGA, which is in agreement with the recent study by Zhu et al, who reported that higher FT4 levels reduce the birthweight and are inversely related to LGA risk [40]. Furthermore, we showed no significant association of FT4 levels with pregnancy complications (GDM/ICP/ PIH) and adverse birth outcomes (PTB/SGA/LGA) after adjusting for maternal age and BMI, excluding PE (adjusted OR: 0.93, 95% CI: 0.88-0.99, p < 0.05).…”
Section: Discussionsupporting
confidence: 92%
“…Elevated BMI has been found in pregnancy women with hypothyroxinemia in many studies [ 14 18 ]. In our study, participants with IMH identified in the first or second trimester also tended to have a higher BMI recorded in the early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the women with hypothyroxinemia were older than the controls, as well as less educated and more likely to smoke during their pregnancy. The Ma’anshan Birth Cohort (MABC) Study in China demonstrated that the risk of having a baby large for gestational age was increased among women with IMH in the second trimester (OR 2.088, 95% CI 1.193–3.654) [ 18 ]. A study in Henan, China found that women with IMH had a significant increase odd of having macrosomia (aOR 2.22, 95% CI 1.13–4.85) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overt hypothyroidism and hyperthyroidism have a high risk of light birth weight or SGA births [11]. Mild thyroid dysfunction, which is more prevalent than overt hypothyroidism, is associated with SGA and LGA according to some studies [12][13][14][15], but not in other studies [16,17]. In euthyroid pregnant women, confirmed [20].…”
Section: Introductionmentioning
confidence: 95%